Functional implications of limited leptin receptor and ghrelin receptor coexpression in the brain - Perello, Mario (2012)
The hormones leptin and ghrelin act in apposition to one another in the regulation of body weight homeostasis. Interestingly, both leptin receptor expression and ghrelin receptor expression have been observed within many of the same nuclei of the central nervous system (CNS), suggesting that these hormones may act on a common population of neurons to produce changes in food intake and energy expenditure. In the present study we explored the extent of this putative direct leptin and ghrelin interaction in the CNS and addressed the question of whether a loss of ghrelin signaling would affect sensitivity to leptin. Using histological mapping of leptin receptor and ghrelin receptor expression, we found that cells containing both leptin receptors and ghrelin receptors are mainly located in the medial part of the hypothalamic arcuate nucleus. In contrast, coexpression was much less extensive elsewhere in the brain. To assess the functional consequences of this observed receptor distribution, we explored the effect of ghrelin receptor deletion on leptin sensitivity. In particular, the responses of ad libitum-fed, diet-induced obese and fasted mice to the anorectic actions of leptin were examined. Surprisingly, we found that deletion of the ghrelin receptor did not affect the sensitivity to exogenously administrated leptin. Thus, we conclude that ghrelin and leptin act largely on distinct neuronal populations and that ghrelin receptor deficiency does not affect sensitivity to the anorexigenic and body weight-lowering actions of leptin. © 2011 Wiley Periodicals, Inc.